Post-COVID Kawasaki-like Multisystem Inflammatory Syndrome Complicated by Herpes Simplex Virus-1 in a Two-Year-Old Child - Emma L. Hodson; Iman Salem; Katherine E. Bradley; Chiamaka L. Okorie; Arthur Marka; Nigel D. Abraham; Nicole C. Pace; Alicia T. Dagrosa; Ryan C. Ratts; Julianne A. Mann (MDPI AG, 2023)
Multisystem inflammatory syndrome in children (MIS-C) is a rare, systemic inflammation following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. We report a case of a 2-year-old male who presented with an exanthem and aberrant laboratory markers, mimicking Kawasaki disease but failing to meet the full diagnostic criteria. His course was further complicated by herpes Simplex Virus-1 (HSV-1) stomatitis.